Redefining more able education key issues for schools - Warwick, Ian; Speakman, Ray (Redefining more able education., 2018)
"Redefining More Able Education is an essential, up to date and challenging introduction to the many factors involved in teaching more able students. Written by Ian Warwick, founder of London Gifted and Talented, and Ray Speakman, this book challenges our understanding of provision for the more able and explores ways in which we can ensure that students reach their full potential."--Provided by publisher.